Advances in Graphene‐Based Liquid Cell Electron Microscopy: Working Principles, Opportunities, and Challenges. Issue 5 (27th February 2019) - Ghodsi, Seyed Mohammadreza; Megaridis, Constantine M.; Shahbazian‐Yassar, Reza; Shokuhfar, Tolou
Abstract: Imaging materials and biological structures in a liquid environment pose a significant challenge for conventional transmission electron microscopy (TEM) due to stringent requirement of ultrahigh vacuum design in the microscope column. The most recent liquid‐cell TEM technique, graphene liquid‐cell (GLC) microscopy, employs only layers of graphene to encapsulate liquid specimens. Recent efforts with GLC–TEM have demonstrated superior imaging resolution of beam‐sensitive specimens. Herein, the parameters that affect the quality of GLC analysis, including the graphene transfer onto TEM grids, are reviewed. Several important factors that affect the in situ TEM imaging of specimens, including the variations in GLC geometries and capillary pressure are discussed. The interaction between the electron beam and the liquid along with the possibility for artifacts or the formation of radical ions is also highlighted in this review. The scientific discoveries enabled by GLC–TEM in the areas of nucleation and growth of crystals, corrosion, battery science, as well as high‐resolution imaging of organelles and proteins are also briefly discussed. Finally, possible future research directions of GLC–TEM and the associated challenges are discussed. The synergistic effort to accomplish the proposed research directions has the potential to yield new discoveries in both materials and life sciences. Abstract : Graphene liquid cell (GLC) transmission electron microscopy is an advanced atomic‐resolution observation technique designed for liquid and hydrated samples. GLCs are attoliter suspensions of proteins, nanoparticles, etc. sealed and protected between thin layers of graphene.